Clostridium ljungdahlii: A Review of the Development of an Industrial Biocatalyst - M. Whitham, Jason; J. Pawlak, Joel; M. Grunden, Amy (Current Biotechnology, 2016)
Background: Autotrophic Clostridia are of considerable interest for use in renewable biofuel and biocommodities production. One such autotrophic Clostridium, Clostridium ljungdahlii, was the first to be identified as an ethanologenic acetogen and has been extensively studied as a microbial catalyst for the conversion of biomass derived synthesis gas to biofuels. To better exploit this bacterium for bulk chemicals (including biofuels) production from CO2, the genome for C. ljungdahlii has been solved and genome-scale modeling performed. In this paper, the historical factors which initiated interest in the microbe, the major scientific findings obtained through the study of this organism, and its utility in the biofuels/biochemical industry are reviewed. Discussion of new areas of study for this organism and biocatalyst improvements of industrial Clostridial strains are also provided. Methods: The available literature on C. ljungdahlii including academic articles and patents have been reviewed and summarized. To better understand why C. ljungdahlii became an industrial biocatalyst for bioethanol production, the history of bioethanol as a fuel and fuel additive in the United States leading up to the bacterium’s discovery and surrounding its development was also reviewed and summarized. Results: The focus of early research on C. ljungdahlii was understanding how to optimize bioethanol production from synthesis gas. Bioethanol was of great interest as a non-petroleum fuel oxygenate and alternative fuel after the oil crisis in the 1970s, and mixing of bioethanol into transportation fuel was mandated in the 2000s. The findings of the initial research efforts with C. ljungdahlii resulted in the incorporation of the first dedicated synthesis gas-derived bioethanol production company. More recent research interest has resulted from the publication of the C. ljungdahlii genome and development of transformation methods, which has fostered research focused on understanding energy conservation at the genetic level and genetically modifying the C. ljungdahlii to produce non-native biocommodities. Despite technical challenges that have prevented commercial production of U.S. mandated quantities of bioethanol from synthesis gas, investment is still being made in developing this technology and new applications of this biocatalyst including electrosynthesis and carboxylic acid reduction are currently under investigation. Conclusion: C. ljungdahlii is an industrial biocatalyst and is a model organism of energy conservation for acetogenic bacteria. The genome sequence of C. ljungdahlii and new genetic tools that have been developed have provided researchers with the resources to fully elucidate the energy conservation processes that operate in this bacterium, determine the electrical pathway which enables C. ljungdahlii to synthesize complex chemicals using electricity, and enhance C. ljungdahlii strains for commercial production of bioethanol and biocommodities.
Keywords: biofuels